A surgical approach for aortic root aneurysm repair: a case report - Feridoun Sabzi; Aghigh Heydari; Javad Azimivaghar; Atefeh Asadmobini (Journal of Medical Case Reports)
Abstract Background The Bentall procedure is the standard treatment for aortic root aneurysm associated with aortic valve disease, but it carries risks of both early perioperative complications and long-term prosthetic-valve-related issues. To overcome these limitations, we applied a novel surgical technique combining Dacron graft wrapping of the aortic root with autologous pericardial valve reconstruction. Case presentation We report a 59-year-old Iranian male with a history of aortic root aneurysm, recurrent peptic ulcers, and intolerance to warfarin. He presented to the emergency department following a car accident, complaining of severe chest pain and displaying anterior chest wall bruising. Transthoracic echocardiography revealed a small intramural hematoma and aneurysmal dilation of the ascending aorta. Emergency surgery was performed using the described novel approach due to suspicion of an intramural aortic aneurysm. The patient’s postoperative course was uneventful, and at 6-month follow-up, he remained clinically stable with only minimal residual aortic regurgitation. Conclusions This case highlights the potential of combining Dacron root wrapping with autologous pericardial valve reconstruction as a viable alternative to conventional prosthetic valve replacement, especially in patients with contraindications to long-term anticoagulation.